2005
DOI: 10.1136/adc.2004.068890
|View full text |Cite
|
Sign up to set email alerts
|

Acid suppression does not change respiratory symptoms in children with asthma and gastro-oesophageal reflux disease

Abstract: Background: Epidemiological studies have shown an association between gastro-oesophageal reflux disease (GORD) and asthma, and oesophageal acid perfusion may cause bronchial constriction. However, no causative relation has been proven. Aim: To assess whether acid suppression would lead to reduced asthma symptoms in children with concomitant asthma and GORD. Methods: Thirty eight children (mean age 10.8 years, range 7.2-16.8; 29 males) with asthma and a reflux index >5.0 assessed by 24 hour oesophageal pH monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 36 publications
2
61
0
11
Order By: Relevance
“…Para crianças com mais de 11 meses, índices de refluxo ≥ 6% são anormais 2 . Em ensaios terapêuticos, de uma forma geral, a seleção de pacientes tem sido feita a partir de índices de refluxo superiores a 5% 9,10 .…”
Section: Treatment Of Gastroesophageal Reflux Diseaseunclassified
See 2 more Smart Citations
“…Para crianças com mais de 11 meses, índices de refluxo ≥ 6% são anormais 2 . Em ensaios terapêuticos, de uma forma geral, a seleção de pacientes tem sido feita a partir de índices de refluxo superiores a 5% 9,10 .…”
Section: Treatment Of Gastroesophageal Reflux Diseaseunclassified
“…Apesar de pretender comprovar se a supressão ácida foi adequada, nova pHmetria foi realizada ao final do tratamento em menos da metade dos pacientes. Nenhuma diferença foi observada entre os grupos em relação aos sintomas de asma, qualidade de vida e medidas da função pulmonar 51 .…”
Section: Asmaunclassified
See 1 more Smart Citation
“…The first placebo-controlled trial of omeprazole in 38 children with uncontrolled asthma and symptomatic GER showed no significant effect of omeprazole on asthma outcomes. 22 In a recent double-blind, placebo-controlled study among 306 school-age children with poorly controlled asthma, the addition of lansoprazole to anti-asthma medications for 24 weeks did not improve respiratory symptoms nor lung function, but was associated with increased adverse events; the results on asthma outcomes were similar in the subgroup with a positive pH study ('silent' GER). The differentiation between acid and non-acidic reflux regarding respiratory symptoms may be important.…”
mentioning
confidence: 57%
“…2 In clinical trials, patients have been enrolled based on a reflux index greater than 5%. 9,10 Treatment of GERD The treatment of GERD should be different from that of common infantile GER. There is evidence that GERD is a lifelong condition.…”
mentioning
confidence: 99%